Pengaruh Religiusitas, Status Sosial Ekonomi dan Love Of Money Pada Persepsi Etis Mahasiswa Akuntansi - Pemayun, Ari Widhiasmana; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2018)
This study aims to examine the influence of religiosity, socioeconomic status and love of money on the ethical perceptions of accounting students. Motivation theory is used to explain the relationship between variables. The population of the study were all active students of non-regular accounting study program class of 2014 Faculty of Economics and Business Udayana University with the number of 187 people. The sample of study was 127 people using Slovin formula. The research used multiple analysis technique. Data were collected by using questionnaire method. Accounting students with high levels of religiosity will have high ethical perceptions. Accounting students with high social status will have low ethical perceptions. Accounting students with high love of money will have high ethical perceptions.